İstanbul büyük saray mozayiği = Istanbul das grosse Byzantinische palastmosaik #Istanbul the great palace mosaic : araştırmalar, onarım ve sergileme #seine erforschung, konservierung und präsentation #the story of its exploration, preservation and exhibition 1983-1997 - Jobst, Werner. (İstanbul)
96s.